Dino-Baby - Mark Sperring (Bharat Bloomsbury, 2013)
It's not easy being a big sister - especially when your new baby brother is a roaring dino baby. There are just SO many things to remember ...Be quiet in the morning, when you first get up. Because crashes, bangs and thuds will wake our dino pup. Shhhhhhhh! Don't play rough and tumble with a little thing like this. Instead be soft and gentle. We all LOVE a dino kiss. Mwaah! But, before long, this big sister grows to love teaching her brother all the grown-up things she knows and, very quickly, life in the dino family is as fun (and chaotic!) as ever.
Keywords: EY - RM -- EY - RM